2004
DOI: 10.1016/j.str.2004.02.028
|View full text |Cite
|
Sign up to set email alerts
|

The Focal Adhesion Targeting Domain of Focal Adhesion Kinase Contains a Hinge Region that Modulates Tyrosine 926 Phosphorylation

Abstract: The focal adhesion targeting (FAT) domain of focal adhesion kinase (FAK) is critical for recruitment of FAK to focal adhesions and contains tyrosine 926, which, when phosphorylated, binds the SH2 domain of Grb2. Structural studies have shown that the FAT domain is a four-helix bundle that exists as a monomer and a dimer due to domain swapping of helix 1. Here, we report the NMR solution structure of the avian FAT domain, which is similar in overall structure to the X-ray crystal structures of monomeric forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 58 publications
1
40
1
Order By: Relevance
“…H1 opening has subsequently been observed in several studies (15,32,33). The conformational strain in this hinge region was experimentally apparent (34,35) and relieved in the open or H1-swapped dimeric conformation of Pro 944 -APP (27,35). The open state would allow Tyr 925 phosphorylation and subsequent binding to Grb2.…”
Section: Focal Adhesion Kinase (Fak)mentioning
confidence: 79%
“…H1 opening has subsequently been observed in several studies (15,32,33). The conformational strain in this hinge region was experimentally apparent (34,35) and relieved in the open or H1-swapped dimeric conformation of Pro 944 -APP (27,35). The open state would allow Tyr 925 phosphorylation and subsequent binding to Grb2.…”
Section: Focal Adhesion Kinase (Fak)mentioning
confidence: 79%
“…Of these two sites, Tyr-925 phosphorylation by Src has been implicated as an important event in adhesion-stimulated FAK signaling by promoting an interaction with the adaptor Grb2 [Schlaepfer et al, 1994;Schlaepfer and Hunter, 1996]. Structural studies showing that Tyr-925 occupies a position in the functional FAK FAT domain where it would be inaccessible indicate that phosphorylation of this site may be of very low stoichiometry in adhesions and occur only in the context of a transient open conformation [Arold et al, 2002;Prutzman et al, 2004]. The mechanism of adhesiondependent activation of FAK appears to involve the interaction(s) of the FERM domain with clustered integrins and/or integrin-associated proteins in nascent adhesion sites, thereby releasing an autoinhibitory interaction of the FERM domain with the FAK kinase domain [Cooper et al, 2003;Dunty et al, 2004;Cohen and Guan, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the FAK FAT domain features helix H1 swapping dynamics and dimer formation (25,40), although the biological importance of such a dimer in the context of full-length FAK is not very clear. However, unlike the FAT domain, our NMR data clearly indicated that PBD existed as a monomer in solution.…”
Section: Solution Structure Of the Git1 Pbd Is A Four-helix Bundle-mentioning
confidence: 99%